Post-Digital Art Practice in Educational Space - Kondratska, Ludmyla; Romanovska, Liudmila; Kravchyna, Tetiana; Ovod, Yuliia; Litynska, Valentyna; Novak, Mykola (Journal of Education Culture and Society, 2024)
Aim. The aim of the article is to validate the pedagogical model for mastering post-digital art practice by future designers. Methods. Its content is determined by the integral anthropotemporal methodology of the organisation of the hybrid educational space, which involves the harmonisation of the intellectual and emotional interaction of the subjects of post-digital art education to project a possible future – Salvation. The priority in this process is the open gestalt of artistic questioning and realisation of the network design of beauty as a spiritual-ontological factor, and the criteria are: the ability to recognise the artistic meaning of the happiness of existence in the polysemy of the text; the competence of theoesthetic modeling of artistic dialogue in the post-digital space and the experience of creating beauty as a good. Results. The implementation of the technological convergence of participatory edutainment and spiritual self-coaching contributed to the mastery of the specified pedagogical model by future performers. The result of its implementation was the acquisition by future performers of post-digital competencies of entropy-informational and adaptive-selective development, performative improvisation, artistic education as an attraction (‘the contemplation’ of an individual in the self-sufficiency of aestheticized Lighting). Conclusion. Thus, mastering the space of post-digital art practice by the future performer involves the activation of his vivid experiential feeling within the artistic sense of oecumenism. A new technonature of the world cannot be built without the human experience of arbitrary paseistic impulse.